(untitled) (Journal of Applied Learning and Teaching, 2021)
This armchair created case is based on the events marketing challenge of selling a perishable service, seats for a Cirque du Soleil winter show series, located temporarily at London’s iconic Royal Albert Hall venue. A real-world advertising agency client campaign brief format is used as the core case body content to provide a concise and rich problem statement. Preparing initially individually and then working in small groups, students are invited to address the campaign brief, building a digitally focussed, integrated marketing communications plan. Students are required to use their marketing knowledge of the RACE and AIDA frameworks, tentpole and content marketing and to apply their understanding of personas and segmentation. The role play format also offers the opportunity for students to reflect on their team working skills.